2020
DOI: 10.1016/j.jbmt.2020.06.039
|View full text |Cite
|
Sign up to set email alerts
|

The reaching movement in breast cancer survivors: Attention to the principles of rehabilitation

Abstract: Introduction: Breast-cancer is leading cause of morbidity and mortality in women. The prognosis and survival rate of women with breast-cancer have significantly improved worldwide; more attention needs to be paid to rehabilitative interventions after surgery. This paper describes use of reaching movement to assess upper limb motorcontrol and functional ability after breast-cancer surgery (BC). Material and Methods: We conducted a cross-sectional observational study consisting of biomechanical evaluation of upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Traditional treatment is conservative, consisting in complex decongestive therapy (CDT) (Paolucci et al, 2020; Sezgin Ozcan et al, 2018). Often, conservative therapy comes with poor quality of life and high costs that may overcome the risks and efforts of apparently more invasive surgical treatments (Fish et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional treatment is conservative, consisting in complex decongestive therapy (CDT) (Paolucci et al, 2020; Sezgin Ozcan et al, 2018). Often, conservative therapy comes with poor quality of life and high costs that may overcome the risks and efforts of apparently more invasive surgical treatments (Fish et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While the abdominally-based approach or tissue expander/implant-based approach provides better upper limb function recovery [6,7], studies have reported that breast expansion due to reconstruction might change the muscle force vector such that the movement quality becomes inaccurate [2,8]. Given that recent rehabilitation studies insisted on including movement quality in important postoperative shoulder functions [9,10], this might be more important than quantitative shoulder functions such as strength or range of motion. Moreover, previous research has focused on donor site morbidities, rather than upper limb function, in the abdominally-based approach [2]; subjective upper limb function is commonly measured by disabilities of the arm, shoulder, and hand (DASH) and Quick DASH (Q-DASH) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Failure to carry out rehabilitation leads to limitations in the participation of ADLs. The movement of the upper limb is qualitatively less fluid (during the reaching function), even if it apparently performs the reaching movement correctly [ 23 ]. Therefore, it is particularly important to study the effect of nursing intervention on controlling the occurrence of postoperative lymphedema.…”
Section: Introductionmentioning
confidence: 99%